Glycoengineering design options for IgG1 in CHO cells using precise gene editing. (27th March 2018) - Schulz, Morten A; Tian, Weihua; Mao, Yang; Van Coillie, Julie; Sun, Lingbo; Larsen, Joachim S; Chen, Yen-Hsi; Kristensen, Claus; Vakhrushev, Sergey Y; Clausen, Henrik; Yang, Zhang
Abstract: Precise gene editing technologies are providing new opportunities to stably engineer host cells for recombinant production of therapeutic glycoproteins with different glycan structures. The glycosylation of recombinant therapeutics has long been a focus for both quality and consistency of products and for optimizing and improving pharmacokinetic properties as well as bioactivity. Structures of glycans on therapeutic glycoproteins are important for circulation, biodistribution and bioactivity. In particular, the latter has been demonstrated for therapeutic IgG1 antibodies where the core α1, 6Fucose on the conserved N -glycan at Asn297 have remarkable dampening effects on antibody effector functions. We previously explored precise gene engineering and design options for N-glycosylation in CHO cells, and here we focus on engineering options possible for N -glycans on human IgG1. We demonstrate stable precise gene engineering of rather homogenous biantennary N -glycans with and without galactose (G0F, G2F) as well as the α2, 6-linked monosialylated (G2FS1) glycoform. We were unable to introduce substantial disialylated glycoforms. Instead we engineered a novel monoantennary homogeneous N -glycan design with complete α2, 6-linked sialic acid capping. All N -glycoforms may be engineered with and without core α1, 6Fucose. The stably engineered design options enable production of human IgG antibodies with an array of distinct glycoforms for testing and selection of optimal design for different therapeutic applications.